FEEDING MANAGEMENT PRACTICES OF DAIRY ANIMALS IN PATAN DISTRICT OF NORTH GUJARAT REGION - Patel, N.B; Patel, J.B; FULSOUNDAR, A. B.; Rao, T. K. S.; Modhi, R.J (Indian Journal of Animal Production and Management, 2017)
A field survey was conducted to collect the first hand information on dairy animalmanagement practices followed by the dairy animal owners of Patan district of northGujarat. Existing feeding management practices were studied through predesigned andpretested questionnaire from 100 dairy animal owners. As far as feeding of green fodder isconcerned, leguminous and non leguminous fodders used by farmers were 76.00 & 24.00percent respectively. About 23.00 per cent farmers used to feed merely compounded cattlefeed, while 77.00 percent farmers used mixture of home-made concentrate with compoundedfeed. Concentrate feeding was significantly (P